أثر القيادة التشاركية على الالتزام التنظيمي والابتكار الإداري دراسة ميدانية في وزارة العمل بسلطنة عمان - خالد بن سعيد بن عبد الله الكتيني الرواس
This study aimed to know the effect of participatory leadership on administrative innovation through the organizational commitment of employees in the Ministry of Labour in the Sultanate of Oman, as this study relied on the use of the descriptive survey approach which is the appropriate approach to the nature of this study and its objectives. The researcher also developed a questionnaire consisting of 76 paragraphs to collect data related to the three variables of the study, and 400 questionnaires were distributed to the targeted category, who are the employees of the Ministry of Labour in the Sultanate of Oman, where they were chosen by using the simple stratified random sample, and the collected data was processed through the study tool by using the statistical software package for social sciences by SPSS program (version 26) to perform descriptive analyzes, and the study also used the (SmpartPLS) program to conduct the standard model (MEASUREMENT MODEL) to evaluate the validity and stability of data and also use the constructive model (STRUCTURAL MODEL) in order to study the structural relationships between the study variables. The results of the study revealed the existence of a direct positive effect of participatory leadership on managerial innovation and the results of the study also showed a positive direct effect of participatory leadership on organizational commitment, in addition, there is an indirect and positive impact of the intermediate variable, the organizational commitment in the relationship between participatory leadership and the administrative innovation. The results were discussed and interpreted in light of the theoretical framework and data of previous studies. Finally, the study included a number of recommendations and proposals for future studies.